Hydroxyl radical footprint analysis of human immunodeficiency virus reverse transcriptase-template.primer complexes. - Metzger, W (1993)
Human immunodeficiency virus type 1 reverse transcriptase protects sugar moieties of a model template.primer DNA in a region from positions +3 to -15 from hydroxyl radical attack. A protected region of equivalent size migrates in concert with the translocating enzyme, as shown by hydroxyl radical footprints of replication complexes after primer extension by 4, 10, and 19 nt. The pattern of these footprints suggests that the DNA template.primer is in the A conformation when complexed with reverse transcriptase. Enhanced accessibility of the DNA template strand around position -15 to hydroxyl radicals indicates a conformational change in the template induced by the C-terminal RNase H-containing domain of p66 reverse transcriptase.